THE RELATIONSHIP BETWEEN MANAGERS’ CREATİVE LEADERSHIP AND SCHOOL CLIMATE - Münevver ÖZTÜRK (Fırat University, 2019)
between school climate and creative leadership.The method of this study is Relational Screening Model with universe of directors and teachers working in İstanbul in 2013-2014. The sample of this research consists of 248 preschool teachers and 23 preschool directors working in the region of Küçükçekmece, Sultanbeyli, Kadıköy, Başakşehir, Esenler, Güngören, Kartal, Ataşehir, Maltepe, Avcılar, Kağıthane, Sarıyer, Bahçelievler, Beşiktaş. Creative Leadership inventory and School Climate Questionnaire were used in this research. The cronbach’s alpha was found as ,98 for Creative Leadership Inventory and ,85 for School Climate Questionnaire.. To analyze the data Independent t Test, Pearson was used. In conclusion a meaningful relationship between creative leadership and school climate was found. But no meaningful relationship between creative leadership and gender was found. Female teachers evaluated their directors’ creative leadership features in a more positive manner than male teachers. Compared to undergraduate teachers, teachers with vocational school degree evaluated their directors’ coaching skills, focusing on cooperative working, problem solving and focusing on critical thinking in a more positive manner. More experienced teachers perceived their directors as creative. According to teachers’ perceptions, male directors are more restrictive; female directors are more directive and warm. Directors with undergraduate degree are found more directive when directing sub dimension of School Climate Questionnaire is analyzed. In the light of these findings, suggestions regarding the relationship between school climate in kindergarten and creative leadership are given.